Group portrait of teenage girls - Unknown:::Creator::::::::::::
Photograph shows a group portrait of teenage girls standing behind tables with painted pictures on them. Three of them are holding paintbrushes. There are many pictures on the wall behind them with the caption below them of "Tempera-Grade" and then the appropriate grade number for the person who painted that picture.